2009
DOI: 10.1186/1471-2458-9-276
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and risk of Metabolic Syndrome in an urban Mexican cohort

Abstract: Background: In the Mexican population metabolic syndrome (MS) is highly prevalent. It is well documented that regular physical activity (PA) prevents coronary diseases, type 2 diabetes and MS. Most studies of PA have focused on moderate-vigorous leisure-time activity, because it involves higher energy expenditures, increase physical fitness, and decrease the risk of MS. However, for most people it is difficult to get a significant amount of PA from only moderately-vigorous leisure activity, so workplace activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 51 publications
4
41
1
2
Order By: Relevance
“…Physical activity was estimated by a validated physical activity questionnaire adapted for the Mexican population [22,23] in which participants were asked about their daily recreational activity. Each activity was given a value in metabolic equivalents (METs) and total METs per day were calculated [10].…”
Section: Methodsmentioning
confidence: 99%
“…Physical activity was estimated by a validated physical activity questionnaire adapted for the Mexican population [22,23] in which participants were asked about their daily recreational activity. Each activity was given a value in metabolic equivalents (METs) and total METs per day were calculated [10].…”
Section: Methodsmentioning
confidence: 99%
“…Each activity was given a value in metabolic equivalent tasks (METs) and total METs/week was computed. Details of the measurement of physical activity are published elsewhere (19).…”
Section: Data Collectionmentioning
confidence: 99%
“…Several large-scale studies in different populations have highlighted the benefit of physical activity in both preventing and treating components of the metabolic syndrome [96][97][98]99 ]. Three recent studies [100 ,101 ,102] have confirmed that exercise lowers several markers of inflammation, including hsCRP, adiponectin, and interleukin (IL)-18.…”
Section: E: Exercisementioning
confidence: 95%